Universidade aberta à terceira idade: efeitos sobre a qualidade de vida percebida - Inouye, Keika (Universidade Federal de São Carlos, 2011)
The education in the old age is intended to promote the acquisition of knowledge that determines the resizing for the fomentation of the quality of life (QoL) from the assumptions of interdisciplinarity, social participation and health promotion. With the objective of evaluating the effects of the University of the Third Age (UTA) from the Fundação Educacional São Carlos (FESC) on the QoL of the participants prior to and after the intervention and one year after their conclusion, we interviewed 56 elderly, divided in groups, thus denominated: (a) Group of students from the UTA-2008 (GA2008): graduating of Module 1 from UTA in 2008, who chose to continue in the program in 2009 even after the end of the mandatory module (Module 1); (b) Group of former students from UTA-2008 (Gex-A2008): graduates of Module 1 from UTA in 2008 that opted not to continue in the program in 2009 after the conclusion of the mandatory module; (c) Group of students from UTA-2009 (GA2009): graduates of Module 1 from UTA in 2009. The instruments for the data collection were: Elderly Characterization Form, Brazilian Economic Classification Criteria, Measure of Quality of Life (QdVDA), Scale to Measure the Satisfaction with the Life and Scale of the Positive and Negative Mood (EAPN). All the obtained data were entered into a database in the Statistical Program for Social Sciences (SPSS), version 13.0, to perform non-parametric statistical analysis. The results showed that: (a) The profile of the researched students from UTA points to a young elderly (M = 68,04 years, DP = 5,78, xmin = 60, xmax = 84), of the female sex (91,1%, n = 51), with a high level of education (30,4% had a bachelor s degree, n = 17) and high social-economic levels (50,0% in level B, n = 28); (b) There is a difference between the total scores on the QoL of the elderly students from UTA before and after the intervention (in the beginning and conclusion of the school year) and this difference is a positive one (Z = -4,541, p < 0,001); (c) There is no difference among the total scores of QoL of the elderly students from UTA in the second year of intervention (follow-up), the total scores remain (Z = -1,477, p = 0,140); (d) There is a difference between the total scores of QoL of the elderly students from UTA who did not attend the program for a year (follow-up) and this difference is a negative one (Z = -2,810, p 0,055); (d) There is a relationship between the perceived changes in the QoL and the socio-demographics characteristics of the students from UTA; (e) There is relationship among the socio-demographics, schooling variables and socio-economic level and the perceptions of QoL, satisfaction with life and moods (positive or negative) of the participants. Since the results pointed that the participation in the UTA program is favorable to the perceptions of the QoL, in terms of improvement or maintenance, we advocate in favor of this type of intervention. Therefore, is necessary that educational programs include the elderly, because the education can be an important source of support to facing another phase of the life cycle.
University of the third age: effects on perceived quality of life
Keywords: Educação especial; Gerontologia; Qualidade de vida; Idosos; Gerontologia educacional; Universidade aberta à terceira idade; Educational gerontology; Quality of life; Elderly; University of the third age; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL